Peningkatan Pembelajaran Instalasi Motor Listrik: Pemanfaatan E-Modul dengan FlipBuilder - Luthfi Zakiral Ghalib; Riki Mukhaiyar (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2023)
This study evaluates the effectiveness of using E-Modules with the FlipBuilder application in learning electric motor installations at SMK Negeri 1 West Sumatra. The results showed a significant improvement in students' understanding, supported by the results of the Independent Samples Test, and confirmed that students' practical abilities were also higher than theoretical understanding measured through experimental post-tests. The main conclusion is that using E-Modules with FlipBuilder effectively improves students' understanding and practical skills, potentially to be applied in the curriculum of technical schools. However, it should be noted that this study had some limitations, such as limited coverage to one school and one subject. Advanced studies involving more schools and subjects can provide greater insight into the effectiveness of these methods. In addition, motivational factors and students' previous experience in the same subject can also be important considerations in future research. This research provides a solid foundation for curriculum development and more effective learning approaches to improve students' understanding and skills in electric motor installation and other engineering fields. The positive impact of this research is felt in the world of education and preparing students for success in an increasingly complex industrial world.